2017
DOI: 10.1128/aem.03206-16
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Relevance of Chromosomal Copy Number Variation in Saccharomyces Yeasts

Abstract: Chromosomal copy number variation (CCNV) plays a key role in evolution and health of eukaryotes. The unicellular yeast Saccharomyces cerevisiae is an important model for studying the generation, physiological impact, and evolutionary significance of CCNV. Fundamental studies of this yeast have contributed to an extensive set of methods for analyzing and introducing CCNV. Moreover, these studies provided insight into the balance between negative and positive impacts of CCNV in evolutionary contexts. A growing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 171 publications
(247 reference statements)
4
60
0
Order By: Relevance
“…Chr III has been repeatedly found to be both completely and partially aneuploid in S. cerevisiae populations adapted to high levels of ethanol (Morard et al, 2019;Voordeckers et al, 2015). Industrial Saccharomyces strains, especially those used for brewing and distilling, frequently experience aneuploidisation, likely for the same reason-the toxicity of high alcohol concentrations in the fermentation vessel (Gorter de Vries, Pronk, & Daran, 2017). Aneuploidy also confers stress tolerance in the spoilage yeast Zygosaccharomyces rouxii, perhaps allowing them to thrive in high salt and sugar environments (Solieri, Dakal, & Bicciato, 2014).…”
Section: Toxic Stressmentioning
confidence: 99%
“…Chr III has been repeatedly found to be both completely and partially aneuploid in S. cerevisiae populations adapted to high levels of ethanol (Morard et al, 2019;Voordeckers et al, 2015). Industrial Saccharomyces strains, especially those used for brewing and distilling, frequently experience aneuploidisation, likely for the same reason-the toxicity of high alcohol concentrations in the fermentation vessel (Gorter de Vries, Pronk, & Daran, 2017). Aneuploidy also confers stress tolerance in the spoilage yeast Zygosaccharomyces rouxii, perhaps allowing them to thrive in high salt and sugar environments (Solieri, Dakal, & Bicciato, 2014).…”
Section: Toxic Stressmentioning
confidence: 99%
“…CS defects such as those observed in our CIC KO lines, including the presence of micronuclei and lagging chromosomes, have been linked to copy number alterations in daughter cells [30][31][32] . To determine whether evidence of copy number defects could be observed in CICdeficient cells, we performed single-cell genome sequencing (DLP+ 33 ) on DNA libraries from the parental CIC WT NHA line and NHA-derived CIC KO lines (A2 and H9 described above, and additional lines B6 and H10).…”
Section: Loss Of Cic In Nha Cells Is Associated With Copy Number Altementioning
confidence: 72%
“…The industrially relevant traits acquired during evolutionary engineering frequently involve the chromosomal copy number variation in S. cerevisiae, a recently reviewed topic (Gorter de Vries, Pronk, & Daran, 2017). For D-xylose utilization, a high number of copies of XylA genes was present in evolved strains and showed a positive impact on xylose utilization (Demeke et al, 2015;Zhou et al, 2012), whereas no such phenomenon has been previously reported in L-arabinose-fermenting S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%